2018
DOI: 10.1016/j.injury.2018.09.009
|View full text |Cite|
|
Sign up to set email alerts
|

Routine pelvic X-rays in asymptomatic hemodynamically stable blunt trauma patients: A meta-analysis

Abstract: In awake, hemodynamically and respiratory stable blunt trauma patients, PE could identify those patients who could safely forgo pelvic X-ray. Selective ordering of pelvic X-ray may lead to a decrease in patient work-up time, lower radiation exposure, and reduce costs. A decision making flow chart is proposed..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…Previous reviews concluded that physical examination was useful for excluding pelvic fracture in alert trauma patients. [7,9] By contrast, the present review revealed that the clinical utility of physical examination varied between settings and level of consciousness. In tertiary care settings such as trauma centers, the clinical bene t of physical examination appeared lower than that of imaging tests for all trauma patients.…”
Section: Strengths and Limitationsmentioning
confidence: 58%
See 3 more Smart Citations
“…Previous reviews concluded that physical examination was useful for excluding pelvic fracture in alert trauma patients. [7,9] By contrast, the present review revealed that the clinical utility of physical examination varied between settings and level of consciousness. In tertiary care settings such as trauma centers, the clinical bene t of physical examination appeared lower than that of imaging tests for all trauma patients.…”
Section: Strengths and Limitationsmentioning
confidence: 58%
“…First, this systematic review was based on a comprehensive literature search. By contrast, two previous systematic reviews of pelvic fracture physical examination [7,9] failed to incorporate several important studies owing to inadequate search. [10,11,39,43,45,50] Second, the current review included study quality assessment and a methodologically rigorous meta-analysis.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Pelvic fracture diagnosis entails physical examination of the pelvis, which is generally performed in prehospital settings or at an emergency department [4][5][6]. It includes the inspection of deformities and the palpation of the pelvis to assess stability; it can be useful as a triage tool or to reduce the frequency of the imaging test [7][8][9]. Nevertheless, some studies [10][11][12] have challenged the reliability of physical examination, in particular, among patients with impaired consciousness.…”
Section: Introductionmentioning
confidence: 99%